"Wizerunek Mikołaja Reja z Nagłowic" Adolfa Nowaczyńskiego - źródła kreacji postaci - Piotrowska, Małgorzata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2003)
In 1905 was publshed a biographical nowel written by Adolf Nowaczyński entitled Portrait of Mikołaj Rej from Nagłowice. While the novel was being written, there were not enough comprehensive and reliable materials about Rej’s life. The purpose of this work is to show pieces of work which were used by Nowaczyński in his novel. Only thanks to searching analysis of those hypothetical available materials the author could manage to establish sources of the hero’s creation. We are sure to say that while writing a novel about Rej, Nowaczyński took some pieces information from Andrzej Trzecieski’s biograhy from the XVI century and Zbigniew n‘aziohtcki’s biography from the XIX century. We can suppose that the author of the Crcation knew the results of Beicikowski’s research.